Implementation of the Islamic Education Curriculum and Learning Materials for Early Childhood in the North Labuhanbatu An-Nur Playgroup - Aziz, Mursal; Hasbie Ashshiddiqi, Muhammad; Ariyanto, Dedi (Eduprof : Islamic Education Journal, 2025)
Lack of understanding and optimal application of the curriculum and learning materials for Islamic Education for early childhood is the main challenge in implementing learning at the An-Nur Playgroup, North Labuhanbatu Regency. This research aims to describe the Islamic education curriculum and learning materials for early childhood in the North Labuhanbatu An-Nur Playgroup. The curriculum is an important part of the learning process, student success is determined by the curriculum implemented by educational institutions. Learning materials as an important part of the curriculum have a role in preparing students according to the educational goals expected by society. The method used in this research is descriptive qualitative, with an observation approach to learning activities, interviews with school principals and teachers as well as documentation of the learning process in the North Labuhanbatu An-Nur Playgroup. The informants in this research were teachers, school principals and institutional managers. The research results show that the Islamic education curriculum and learning materials for early childhood implemented in the An-Nur Play Group include teaching about morals, worship, as well as introducing the values ​​of the Koran and hadith through methods that are appropriate to the child's development stage. The implementation of this curriculum also involves play activities which function as a means of introducing Islamic teachings in a way that is fun and easy for children to understand. Overall, the implementation of this curriculum is expected to produce a young generation who is not only intellectually intelligent but also has a strong character and is based on Islamic teachings. The implementation of the Islamic education curriculum in early childhood, especially in the North Labuhanbatu An-Nur Playgroup, has had a positive impact on the development of children's character based on Islamic values. By integrating moral education, worship, and introduction to the values ​​of the Koran and hadith from an early age, this curriculum is expected to form individuals who are not only intellectually intelligent, but also have good morals and spirituality. The results of this study are expected to be a reference in developing more effective Islamic Education learning strategies that are in accordance with the developmental stages of early childhood at the An-Nur Playgroup, North Labuhanbatu.